(untitled) (Tumou Tou: Jurnal Pengabdian Masyarakat, 2025)
Drainage channels are one of the infrastructures for the community environment because their function is to drain water on the surface that comes from rainwater as quickly as possible to the receiving water body. Ecodrainage is a new concept for handling sustainable urban drainage systems that pay attention to environmental conditions and carrying capacity and has the principle of absorbing as much water as possible into the soil. Mentoring is planned for students at SMA Negeri 4 Manado so that they can understand and be aware early on about sustainable technology in an environmentally friendly drainage system, which will then be called ecodrainage, in order to minimize the probability of flooding. This program aims to provide mentoring and training in analyzing and implementing a sustainable drainage system and planning the development of an environmentally friendly drainage system (ecodrainage) for students at SMA Negeri 4 Manado. The method that will be used in mentoring and training is an evaluation of the existing condition of the drainage system in the planned area by comparing the condition of the existing channel with the planned channel and planning ecodrainage with selected technologies, namely rainwater harvesting, to reduce the discharge of rainwater runoff, which is a burden on the drainage channel.